Support the Barcelona Congress (leaflet)
SUPPORT THE BARCELONA CONGRESS The International Revolutionary Socialist Congress takes place in Barcelona in February. It is being organised in the heart of the Revolution and in the struggle against Fascism by the International Bureau for Revolutionary Socialist Unity and the Spanish Workers' Party for Marxist Unity. The Congress will make decisions on vital questions now facing the International Proletariat, on the STRUGGLE AGAINST WAR AND FASCISM ON GIVING EFFECTIVE AID TO THE SPANISH REVOLUTION and ON ACHIEVING REVOLUTIONARY SOLIDARITY ON A WORLD-WIDE SCALE Events, social and political, crowd upon us and new historical upheavals threaten every worker. Action is essential. THE R.S.P. IS DETERMINED TO PLAY ITS MOST VIGOROUS PART IN COMING EVENTS, IN THE INTERESTS OF THE PROLETARIAT, AND FOR THIS REASON PARTICIPATES IN THE BARCELONA CONGRESS. The Party urges your most generous financial support in making it possible to send a delegation to this important Congress. Send a Donation NOW. Use the form below : ............................................................ Tear Here .......................................................... I enclose £ : : . NAME ADDRESS DATE 15/3/8/226